Produção de nanocompósitos de celulose bacteriana e hidroxiapatita como rota para valorização de resíduos agroindustriais - Duarte, Eden Batista (2014)
Environmental issues have supported the interest in renewable sources and agroindustrial residues became a significative resource for the production of new materials, chemicals and energy. This thesis proposes the use of agroindustrial residues (cashew juice and sisal liquid waste) to obtain bacterial cellulose (BC) for further elaboration of nanocomposites with hydroxyapatite (HA). The production of BC membranes by Gluconacetobacter hansenii occurred in Hestrin & Schramm medium (containing mainly glucose as carbon sources), cashew juice and sisal liquid waste cultivated under static conditions. After the incubation period, the BC membranes were purified and nanocomposites prepared by successive immersion of the purified membranes in solutions of Calcium Chloride (CaCl2), and Sodium Phosphate (NaHPO4), followed by drying and subsequent characterization. The materials obtained were characterized by X-ray Diffraction (XRD), Fourier Transform Spectroscopy (FTIR), Energy Dispersive Spectroscopy (EDS), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM) and mechanical tests. Additionally, in vitro tests were performed for nanocomposites. The results showed the production of cellulose from the three substrates studied, without the need for further supplementation or pH change. In all characterizations, structure and typical behavior of bacterial cellulose were found. Scanning electron microscopy allowed investigation of morphology of cellulose fibers and observation of deposition of hydroxyapatite particles. The mechanical properties of nanocomposites based on BC and HA showed decrease in elastic modulus compared to pure films with increase in elongation. The composites showed bioactivity, stability in solution and the adsorption capacity of proteins, which lead to potential biocompatibility of these materials.